Percutaneous Nephrolithotomy: A Single Center Experience of 162 Cases of Standard Percutaneous Nephrolithotomy (Medical Forum Monthly, 2024)
Objective: This study aims to share our experience of Percutaneous nephrolithotomy regarding its safety and efficacy for renal stones in a tertiary care hospital.Study Design: A Retrospective StudyPlace and Duration of Study: This study was conducted at the department of Urology Unit IKD Peshawar from July 2021 to July 2022.Methods: This retrospective study included all those patients who underwent Percutaneous nephrolithotomy in the Urology Unit. The data was collected retrospectively from the hospital record system and analysis was done with IBM SPSS version 20.Results: A total of 162 patients including 67.3% male and 32.7% female were part of this study. Fifty-five percent of the patients had a previous history of renal stones. Pre-operative Ultrasound findings were multiple stones in 54.3%, single stones in 40.1%, staghorn stones in 3.7%, a duplex system in 1.2 %, and horseshoe kidney in 0.6% (n=1). Sixty percent had stone sizes ranging from 15 mm to 30mm, 22.8% had stone sizes less than 15mm and 16.7% had stone sizes greater than 30mm. In the majority, the location of stones was renal pelvis (46.3%), lower pole 18.5%, Pelvis plus lower pole 16%and staghorn 7.4%. Pre-operative mean Hemoglobin was 12.9g/dl and post-operative 11.8g/dl with a mean drop of 1.1g/dl. Complete stone clearance was achieved in 86.4%, partial stone clearance in 11.7% and the procedure was abandoned in 1.9% (n=3). The majority of the procedure was uneventful (87.7%) while 12.3% had complications in the form of bleeding requiring blood transfusion 5.5%(n=9), sepsis 3.08%, pleural injury 1.2%, peritoneal injury and stone fragment migration to ureter with subsequent ureteral obstruction 0.61% (n=1) each. One patient died of sepsis with multi-organ failure. The mean hospital stay was 3.06 days with a minimum of 2 days and a maximum of 11 days.Conclusion: Percutaneous nephrolithotomy is an effective way of treating a wide range of stone sizes, in different renal locations, in anomalous kidneys with a high clearance rate and acceptable complication rate.